Impact of Enterprise Resource Planning (ERP) Systems on Supply Chain Performance: An Applied Study on the Jordanian Pharmaceutical Companies - AbuDifallah, Mohammad; AlShaar, Ishaq (Jordan Journal of Business Administration, 2017)
This study aimed to identify the impact of enterprise resource planning (ERP) systems (integration, materials management, production planning, system quality and control) on supply chain performance (response and cooperation, economic cost, consumer satisfaction and the relationship with suppliers) in the Jordanian pharmaceutical companies. The population of the study consisted of all users of ERP systems in the Jordanian pharmaceutical companies. A purposive sample was used to collect data from (180) ERP system users. Data was analyzed using a number of statistical techniques, including (frequencies, percentages, standard deviations, multiple regression, principle factor analysis and Kruskal-Wallis). The study revealed that the level of application of ERP systems was high and the supply chain performance level was high in the Jordanian pharmaceutical companies. Another significant result of this study indicated that the ERP system represented by (integration, materials management, production planning, system quality and control) positively affects the supply chain performance represented by (response and cooperation, economic cost, consumer satisfaction and relationship with suppliers). However, the study did not find any differences in the level of ERP system application related to years of experience of those working on (ERP) systems.